Pengaruh Penerapan Model Active Learning Tipe Everyone is A Teacher Here terhadap Keaktifan Belajar Pendidikan Agama Islam Siswa di SMP N 1 Panti Kabupaten Pasaman - Febi Muliani; Arifmiboy Arifmiboy; Iswantir M; Charles Charles (Hikmah : Jurnal Studi Pendidikan Agama Islam, 2024)
This research was conducted because researchers saw that PAI teachere still appilied conventional learning models during the Islamic religious education learning process. Researchers saw that many students did not play an active role during the question and answer session, and lacked the courage to express their opinions. during the learning process. The purpose of conducting this research is to find out whether there is an influence of implementing the Everyone Is Teacher Herr Active Learning Model on students' active learning in Islamic religious education at SMP N 1 Panti, Pasaman Regency. The type of research used by researchers is quasi-experimental research. The population of this research is all class VIII students, totaling 129 students. The technique used in sampling by researchers was odd semester UTS scores and then a normality test and homogeneity test were carried out and the samples were determined randomly. Data collection was carried out by researchers using a questionnaire, the analysis technique was carried out using the f-test and t-test. The results of the analysis using the f test in the experimental class had a value of 4.701 with a significance level of 0.040-0.005 so it could be concluded that there was an influence, while the results of the analysis using the t in the control class there is a t-hit value of 4.357> t-table 2.064 and a significance level of 0.000 0.05 and it can be concluded that there is differences in student activity.